2018
DOI: 10.1002/dc.24062
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology in Mozambique: Report of a 15‐year experience

Abstract: Background Fine needle aspiration cytology (FNAC) is an important diagnostic tool in a range of medical settings. It is fast, quick and a highly accurate diagnostic method and can be used, in settings with minimal laboratory infrastructures. Methods In this report, we describe the experience in the use of FNAC since it is introduction in 1996 in the Anatomical Pathology Service of the Maputo Central Hospital (MCH), along with more detailed data referring to 2009‐2010. Results The number of FNAC analyses increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…42 Here, we demonstrated that this assessment can be made in lowresource settings, using cell blocks from FNAC, which are usually available and much less expensive than core needle biopsies. 23 International societies increasingly recommend the use of neoadjuvant therapy, especially for HER2-positive tumours and TNBC. 6 Therefore, if the physician has access to biomarker determination and is aware that the patient has TNBC, neoadjuvant chemotherapy combining anthracyclines, taxanes and platinum salts could be recommended, as the addition of platinum salts increases the chance of achieving a pCR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…42 Here, we demonstrated that this assessment can be made in lowresource settings, using cell blocks from FNAC, which are usually available and much less expensive than core needle biopsies. 23 International societies increasingly recommend the use of neoadjuvant therapy, especially for HER2-positive tumours and TNBC. 6 Therefore, if the physician has access to biomarker determination and is aware that the patient has TNBC, neoadjuvant chemotherapy combining anthracyclines, taxanes and platinum salts could be recommended, as the addition of platinum salts increases the chance of achieving a pCR.…”
Section: Discussionmentioning
confidence: 99%
“…42 Here, we demonstrated that this assessment can be made in low-resource settings, using cell blocks from FNAC, which are usually available and much less expensive than core needle biopsies. 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Cytopathologists in many LMICs have also taken the call to action to train in performing and interpreting FNAB to expand access to diagnostic services for patients. 15,17,18 Recognition of the simplicity of performing the FNAB has made it a valuable choice for implementation in LMICs. However, severe shortages of both laboratories and personnel further hinder the diagnostic process, potentially resulting in inappropriate treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In low-resource settings, fine needle aspiration (FNA) is an important tool to determine the cause of suspicious lymphadenopathy [1][2][3]. Previous reports highlight the utility of this procedure in high HIV and tuberculosis (TB) burden regions [4][5][6].…”
Section: Introductionmentioning
confidence: 99%